Usage, benefits and barriers of human resource information system in universities. Issue 4 (4th November 2014) - Bamel, Nisha; Kumar Bamel, Umesh; Sahay, Vinita; Thite, Mohan
Abstract : Purpose: – The purpose of this paper is to examine the university teaching staff's perception about functions, benefits and barriers of human resource information system (HRIS). It also aims to explore the relevance of attitudinal/demographic diversity with focused HRIS dimensions. Design/methodology/approach: – A 26-item questionnaire was developed on the basis of similar research studies. Responses were collected through electronic mail from 90 faculty members of seven state universities in India. Descriptive statistics along with t -test and analysis of variance were used to answer the research questions. Findings: – The results of the study reported that HRIS is mostly used for administrative purpose and not taken as strategic requirement. Results also revealed that the perceived functions, benefits and barriers in adoption of HRIS do not vary group-wise. Research limitations/implications: – The findings of the study potentially can help in developing and implementing of HRIS in similar types of organizations. Originality/value: – Past literature on HRIS mainly comes from the developed countries and is confined to for-profit organizations. The present study is among the few that coherently took up the issue from non-profit organizations, i.e. universities of a developing country.